Bulletin of the Walters Art Gallery, 1950: Recent Acquisitions - Anonymus, A.
1. Bronze ibex-bull, made to support some object, from Azarbaigan — 2. Strip of bronze relief (fragment from the Bronze Gates of Balawat) representing Assyrian soldiers transporting thick poles over a mountain.